Using Modern Neuroscience to Inform Opioid Use and Abuse Liability in Adolescents. (March 2019) - Napier, T. Celeste; Persons, Amanda L.
Abstract : Opioid abuse and overdosing have reached epidemic status in the United States, and this epidemic has profound negative effects on the lives of adolescents and their families. A combination of readily available opioids (including illicit opioids, such as heroin, and overprescribed prescription opioid-based painkillers) and an abuse vulnerability inherent to adolescence drives the problem. The pharmacology of opioids in the context of adolescent brain neurobiology helps explain the enhanced vulnerability to drug abuse experienced by the young. This report overviews these topics as they relate to orthopaedic procedures employed for adolescent patients.